Molecular and clinical profile of von Willebrand disease in Spain (PCM–EVW–ES): Proposal for a new diagnostic paradigm - Batlle, Javier; Pérez-Rodríguez, Almudena; Corrales, Irene; López-Fernández, María Fernanda; Rodríguez-Trillo, Ángela; Lourés, Esther; Cid, Ana Rosa; Bonanad, Santiago; Cabrera, Noelia; Moret, Andrés; Parra, Rafael; Mingot-Castellano, María Eva; Balda, Ignacia; Altisent, Carmen; Pérez-Montes, Rocío; Fisac, Rosa María; Iruín, Gemma; Herrero, Sonia; Soto, Inmaculada; Rueda, Beatriz de; Jiménez-Yuste, Víctor; Alonso, Nieves; Vilariño, Dolores; Arija, Olga; Campos, Rosa; Paloma, María José; Bermejo, Nuria; Toll, Teresa; Mateo, José; Arribalzaga, Karmele; Marco, Pascual; Palomo, Ángeles; Sarmiento, Lizheidy; Iñigo, Belén; Nieto, María del Mar; Vidal, Rosa; Martínez, María Paz; Aguinaco, Reyes; César, Jesús María; Ferreiro, María; García-Frade, Javier; Rodríguez-Huerta, Ana María; Cuesta, Jorge; Rodríguez-González, Ramón; García-Candel, Faustino; Cornudella, Rosa; Aguilar, Carlos; Borràs, Nina; Vidal, Francisco (Thrombosis and Haemostasis, 2016)
The diagnosis of von Willebrand disease (VWD) remains difficult in a significant proportion of patients. A Spanish multicentre study investigated a cohort of 556 patients from 330 families who were analysed centrally. VWD was confirmed in 480. Next generation sequencing (NGS) of the whole coding VWF was carried out in all recruited patients, compared with the phenotype, and a final diagnosis established. A total of 238 different VWF mutations were found, 154 were not included in the Leiden Open Variation Database (LOVD). Of the patients, 463 were found to have VWF mutation/s. A good phenotypic/ genotypic association was estimated in 96.5 % of the patients. One hundred seventy-four patients had two or more mutations. Occasionally a predominant phenotype masked the presence of a second abnormality. One hundred sixteen patients presented with mutations that had previously been associated with increased von Willebrand factor (VWF) clearance. RIPA unavailability, central phenotypic results disagreement and difficult distinction between severe type 1 and type 3 VWD prevented a clear diagnosis in 70 patients. The NGS study facilitated an appropriate classification in 63 of them. The remaining seven patients presented with a VWF novel mutation pending further investigation. In five patients with a type 3 and two with a type 2A or 2B phenotype with no mutation, an acquired von Willebrand syndrome (AVWS) was suspected/confirmed. These data seem to support NGS as a first line efficient and faster paradigm in VWD diagnosis.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: VWD; VWF; NGS; phenotype; genotype